2023
DOI: 10.1590/s1519-994020230024
|View full text |Cite
|
Sign up to set email alerts
|

Production costs and economic indicators in the complete cycle of crossbred dairy calves

Diogo da Silva BELIZÁRIO,
Rafael Alves da Costa FERRO,
Diogo Alves da Costa FERRO
et al.

Abstract: The complete rearing cycle of dairy calves is not yet widely adopted by rural producers, possibly because they do not perceive these animals as potential meat producers or are unaware of their production capabilities. This study aimed to assess the economic viability of rearing dairy calves through their entire growth cycle. Sixteen Holstein × Gyr crossbred animals were assessed, originating from dairy farming, with an average initial weight of 40.67 ± 5.27 kg and slaughtered at 10 months of age, reaching a fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…Increasing the nutritional value of feed by 10% can lead to a 43% increase in profits, raising livestock with low RFI can reduce feed consumption by 12%, reduce methane emissions by 30% and reduce manure by 17% [15]. An assessment of the economic feasibility of raising cross-bred dairy calves (Holstein × Gyr) throughout their growth cycle from birth with an average initial weight of 40.67 kg and slaughtered at the age of 10 months, reaching a final weight of 320.4 kg showed that growing on feedlots on a mixed diet without the inclusion of coarse feed provided a large profit, significant potential in increasing the carcass weight and quality [16].…”
Section: Introductionmentioning
confidence: 99%
“…Increasing the nutritional value of feed by 10% can lead to a 43% increase in profits, raising livestock with low RFI can reduce feed consumption by 12%, reduce methane emissions by 30% and reduce manure by 17% [15]. An assessment of the economic feasibility of raising cross-bred dairy calves (Holstein × Gyr) throughout their growth cycle from birth with an average initial weight of 40.67 kg and slaughtered at the age of 10 months, reaching a final weight of 320.4 kg showed that growing on feedlots on a mixed diet without the inclusion of coarse feed provided a large profit, significant potential in increasing the carcass weight and quality [16].…”
Section: Introductionmentioning
confidence: 99%